Overwintering biology and limits of cold tolerance in larvae of pistachio twig borer, Kermania pistaciella - Mollaei, M; Izadi, H; Šimek, P; Koštál, V (Bulletin of entomological research, 2016)
Pistachio twig borer, Kermania pistaciella is an important pest of pistachio trees. It has an univoltine life-cycle and its larvae tunnel and feed inside pistachio twigs for almost 10 months each year. The last larval instars overwinter inside the twigs. Survival/mortality associated with low temperatures during overwintering stage is currently unknown. We found that overwintering larvae of the Rafsanjan (Iran) population of K. pistaciella rely on maintaining a stably high supercooling capacity throughout the cold season. Their supercooling points (SCPs) ranged between -19.4 and -22.7°C from October to February. Larvae were able to survive 24 h exposures to -15°C anytime during the cold season. During December and January, larvae were undergoing quiescence type of dormancy caused probably by low ambient temperatures and/or changes in host tree physiology (tree dormancy). Larvae attain highest cold tolerance (high survival at -20°C) during dormancy, which offers them sufficient protection against geographically and ecologically relevant cold spells. High cold tolerance during dormancy was not associated with accumulation of any low-molecular mass cryoprotective substances. The SCP sets the limit of cold tolerance in pistachio twig borer, meaning that high mortality of overwintering populations can be expected only in the regions or years where or when the temperatures fall below the average larval SCP (i.e., below -20°C). Partial mortality can be expected also when temperatures repeatedly drop close to the SCP on a diurnal basis.
Keywords: Pistacia; supercooling; Metabolomics; Adaptation, Physiological; larva; cold hardiness; nízká teplota; metabolomika; zvířata; Cold Temperature; roční období; metabolomics; Moths; Seasons; můry; fyziologická adaptace; Lepidoptera; Larva; Animals; quiescence